Jurisprudence of the rights of Muslim minorities and the reasons for their care - Suleiman, Mahmoud Sayed Ahmed (Journal of Humanities & Social Sciences, 2017)
The rights of Muslim minorities and the reasons for caring about them. This research is concerned about the rights of Muslim minorities in countries and regions in which such minorities are found. The aim of the study is to shed light on Islamic jurisprudence in this matter. One of the interesting and important laws of Islam that concern the Muslim minorities and those who embraced it is that Islam has special flexible laws and regulations that are less severe and not as strict as those in the Muslim countries, and take into considerations the circumstances of Muslim minorities. This indicates that Islamic laws are applicable and adjustable, to a certain extent, in accordance with the time and the nature of the place. The importance of the rights of Muslim minorities in Islam is emphasized by the presence of a special jurisprudence for them known as ‘’ jurisprudence of minorities ’’ which takes into account the circumstances of Muslim minorities in non-Muslim countries. Such jurisprudence permits the Muslim minorities to do certain things that are prohibited for Muslims living in Muslim countries. The jurisprudence of minorities requires the concerned scholars to know the special and flexible jurisprudential rules in order help the Muslim minorities conduct their worships and lives in a flexible and easy manner. For example there is as a rule known as `hardship brings easing` which enables the Muslim minorities to adjust the strict rules under certain circumstances. It is important to support the Islamic centers in non-Muslim countries which provide the Muslim minorities with all the necessary information about how to conduct their worships and lives under certain circumstances. One of the leading countries in supporting such centers is Saudi Arabia.